Pengaruh Variasi Diameter Kawat MetalInertGas(mig) TerhadapKetangguhanDan Struktur Mikro Material Baja ST37 - Irvan kirannuan; Risa Bernadip Umar; M.Ilham Nur (Fakultas Teknik UPRI, 2026)
This study aims to determine the effect of variations in the diameter of the Metal Inert Gas (MIG) welding wire on the toughness and microstructure of ST 37 steel. The research methods used include laboratory experiments with specimen making and toughness testing using the Charpy method, as well as microstructure analysis using an optical microscope. The variations in wire diameter used in this study were 1.2 mm, 0.8 mm, and 0.6 mm, as well as untreated conditions (normal).Research methods include field research using observation methods, namely by making specimens. Library research is intended to process data obtained in the field, obtain knowledge and theoretical basis from several literature and research results of other people with the problem being studied.